Due note filologiche di greco biblico - Pierri, R. (Liber Annuus, 2006)
Abstract The first part of this contribution focuses on the interpretation of the conjunction oti in Gal 4:6. The adduced arguments induce it to be considered as a casual conjunction. A conclusive note refers to a possible exegetic implication of the proposed reading, regarding Paulʼs relation to the Holy Spirit in the Acts of the Apostles. The second part attempts to demonstrate that the article of a complement in attribuive (second) position may have construction according to the sense (in number) with its antecedent, where the participle of eijmiv is understood or of another verb derived from the context.",